2017
DOI: 10.1038/s41598-017-16684-9
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Mitigation Potential of Plug-in Hybrid Electric Vehicles larger than expected

Abstract: The actual contribution of plug-in hybrid and battery electric vehicles (PHEV and BEV) to greenhouse gas mitigation depends on their real-world usage. Often BEV are seen as superior as they drive only electrically and do not have any direct emissions during driving. However, empirical evidence on which vehicle electrifies more mileage with a given battery capacity is lacking. Here, we present the first systematic overview of empirical findings on actual PHEV and BEV usage for the US and Germany. Contrary to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 12 publications
2
42
0
Order By: Relevance
“…A Norwegian study also reported that only 16% of PHEV drivers plug their vehicle in every day (Figenbaum and Kolbenstvedt, 2016). However, a recent, broader analysis of PEV usage data estimates that PHEVs have tended to be substantially powered by grid electricity rather than gasoline (Plötz et al, 2017a). Results from this study which contains several data sets totalling more than 70,000 PHEVs with around 40 miles of driving range found that they can achieve similar eVMT as BEVs with 100 miles of range.…”
Section: Charge Point Activity and Locationsmentioning
confidence: 78%
See 1 more Smart Citation
“…A Norwegian study also reported that only 16% of PHEV drivers plug their vehicle in every day (Figenbaum and Kolbenstvedt, 2016). However, a recent, broader analysis of PEV usage data estimates that PHEVs have tended to be substantially powered by grid electricity rather than gasoline (Plötz et al, 2017a). Results from this study which contains several data sets totalling more than 70,000 PHEVs with around 40 miles of driving range found that they can achieve similar eVMT as BEVs with 100 miles of range.…”
Section: Charge Point Activity and Locationsmentioning
confidence: 78%
“…Plug-in electric vehicles (PEVs), which include both battery electric vehicles (BEVs) and plug in hybrid electric vehicles (PHEVs), are more efficient and less polluting than the majority of internal combustion engine vehicles (ICEVs) (Jochem et al, 2015a;Nordelöf et al, 2014;Offer et al, 2011;Plötz et al, 2017a;Poullikkas, 2015). They will need to increase market shares to have an impact on urban air pollution, energy consumption, and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…This follows the assumption that a PHEV with a high mileage in zero-CO 2 -emission-mode can be considered to drive predominantly electrically and should be promoted like a BEV. A recent study even revealed that PHEVs with about 60 km of real-world range currently electrify as many annual vehicles' kilometers as BEV with a much smaller battery [18]. Such long-range PHEV will help to convince a larger share of the population to drive an electric vehicle as they help to overcome driving range limitations in areas with limited (public) charging infrastructure and to manage the one or two long distance vacation trips per year.…”
Section: The Netherlandsmentioning
confidence: 99%
“…The trial also focussed on early adopters as a deliberate feature of the study design (Vilimek et al, 2013, Turrentine et al, 2011, and participation was conditional on successful application and on paying a monthly lease, raising possible questions of self-selection. (Plötz et al, 2017).…”
Section: Nature Of the Evidence Foundmentioning
confidence: 99%
“…PHEVs with 40km and 120km ranges had utility factors of 50% and 80% respectively (Plötz et al, 2017).…”
Section: Electric Range In Phevsmentioning
confidence: 99%